Genome-wide survey and comprehensive expression profiling of Aux/IAA gene family in chickpea and soybean - Singh, Vikash K.; Jain, Mukesh (Frontiers in Plant Science, 2015)
Auxin plays a central role in many aspects of plant growth and development. Auxin/Indole-3-Acetic Acid (Aux/IAA) genes cooperate with several other components in the perception and signaling of plant hormone auxin. An investigation of chickpea and soybean genomes revealed 22 and 63 putative Aux/IAA genes, respectively. These genes were classified into six subfamilies on the basis of phylogenetic analysis. Among 63 soybean Aux/IAA genes, 57 (90.5%) were found to be duplicated via whole genome duplication (WGD)/segmental events. Transposed duplication played a significant role in tandem arrangements between the members of different subfamilies. Analysis of Ka/Ks ratio of duplicated Aux/IAA genes revealed purifying selection pressure with restricted functional divergence. Promoter sequence analysis revealed several cis-regulatory elements related to auxin, abscisic acid, desiccation, salt, seed and endosperm, indicating their role in development and stress responses. Expression analysis of chickpea and soybean Aux/IAA genes in various tissues and stages of development demonstrated tissue/stage specific differential expression. In soybean, at least 16 paralog pairs, duplicated via WGD/segmental events, showed almost indistinguishable expression pattern, but eight pairs exhibited significantly diverse expression patterns. Under abiotic stress conditions, such as desiccation, salinity and/or cold, many Aux/IAA genes of chickpea and soybean revealed differential expression. qRT-PCR analysis confirmed the differential expression patterns of selected Aux/IAA genes in chickpea. The analyses presented here provide insights on putative roles of chickpea and soybean Aux/IAA genes and will facilitate elucidation of their precise functions during development and under abiotic stress conditions.